Isolated convergence-retraction nystagmus secondary to intralesional haemorrhage of a pineal cyst: an easily missed neurological finding with potentially life-threatening consequences. Issue 9 (14th September 2020) - Woodward, Kristine; Sitaram, Amith; Peters, Steven
Abstract : This case report describes a patient who presented to the emergency department with intermittent visual disturbance and was found to have convergence-retraction nystagmus. This occurred in the setting of supratherapeutic anticoagulation on warfarin for an aortic dissection graft repair. Urgent imaging demonstrated haemorrhagic transformation of a previously identified incidental pineal cyst. After close monitoring given the risk of secondary hydrocephalus, the patient was discharged in stable condition with symptom resolution and without any further significant complications. This case report highlights the importance of identifying subtle clinical findings and the risk of secondary haemorrhage of pineal cysts when on anticoagulation. While the risk of secondary hydrocephalus is a significant concern, clinically stable patients can be followed without need for neurosurgical intervention.